New species of Platypalpus from Hebei province, China (Diptera: Empididae) - Yang, Ding; Li, Weihai (Zootaxa, 2005)
The genus Platypalpus Macquart is reported from Hebei province for the first time. The following three species are described as new to science: P. hebeiensis n. sp., P. acutatus n. sp. and P. xiaowutaiensis n. sp. A key to the species of the genus from Hebei is presented.